X-ray microtomography imaging of craniofacial hard tissues in selected reptile species with different types of dentition. (7th March 2022) - Kavková, Michaela; Šulcová, Marie; Zikmund, Tomáš; Pyszko, Martin; Kaiser, Jozef; Buchtová, Marcela
Abstract: Background: Reptiles exhibit a large heterogeneity in teeth morphology. The main variability comprises the different tooth shape, the type of tooth attachment to the underlying bone, or the ability to replace the teeth. Findings: Here, we provide full datasets of microtomography scans and 3D models of reptilian dentitions and skulls. We selected representative species for each of 9 reptilian families on the basis of their characteristic dental features. Because there are ≥4 different types of tooth-bone attachments, ranging from the mammalian-like thecodont attachment found in crocodilians to the simple acrodont implantation observed in some lizards, we aimed to evaluate species with different types of tooth-bone attachments. Moreover, another interesting feature varying in reptilian species is the complexity of tooth shape or the number of tooth generations, which can be associated with the type of tooth attachment to the jawbone. Therefore, selected model species also include animals with distinct tooth morphology along the jaw or different number of tooth generations. The development of tooth attachment and relationship of the tooth to the jaw can be further analysed in detail on a large collection of pre-hatching stages of chameleon. Next, we introduce different possibilities for how these datasets can be further used to study tooth-bone relationships or tooth morphology in 3D space. Moreover, these datasets can be valuable for additional morphological and morphometric analyses of reptilian skulls or their individually segmented skeletal elements. Conclusions: Our collection of microcomputed tomography scans can bring new insight into dental or skeletal research. The broad selection of reptilian species, together with their unique dental features and high quality of these scans including complete series of developmental stages of our model species and provide large opportunities for their reuse. Scans can be further used for virtual reality, 3D printing, or in education.